Fertility and economic instability: The role of unemployment and job displacement - Emilia Del Bono; Andrea Weber; Rudolf Winter-Ebmer (University of Essex, Institute for Social and Economic Research (ISER), 2014)
In this paper we study the separate effects of unemployment and job displace- ment on fertility in a sample of white collar women in Austria. Using an instru- mental variables approach we show that unemployment incidence as such has no negative effect on fertility decisions, but the very fact of being displaced from a career-oriented job has. Fertility rates for women affected by a firm closure are significantly below those of a control group, even after six years, and this is so irrespective of the incidence or the duration of the associated unemployment spell.
Keywords: J13; J64; J65; J24; 330; fertility; unemployment; firm closures; human capital